Post-plasma quenching to improve conversion and energy efficiency in a CO2 microwave plasma. (15th February 2023) - Mercer, E.R.; Van Alphen, S.; van Deursen, C.F.A.M.; Righart, T.W.H.; Bongers, W.A.; Snyders, R.; Bogaerts, A.; van de Sanden, M.C.M.; Peeters, F.J.J.
Graphical abstract: Highlights: Post-plasma constriction of a CO2 microwave plasma enhances conversion and energy efficiency. Increased performance is the result of enhanced molecular transport from the plasma region. 3D CFD simulations showed that the constriction encourages product retention, which results in increased performance. Abstract: Transforming CO2 into value-added chemicals is crucial to realizing a carbon–neutral economy, and plasma-based conversion, a Power-2-X technology, offers a promising route to realizing an efficient and scalable process. This paper investigates the effects of post-plasma placement of a converging–diverging nozzle in a vortex-stabilized 2.45 GHz CO2 microwave plasma reactor to increase energy efficiency and conversion. The CDN leads to a 21 % relative increase in energy efficiency (31 %) and CO2 conversion (13 %) at high flow rates and near-atmospheric conditions. The most significant performance improvement was seen at low flow rates and sub-atmospheric pressure (300 mbar), where energy efficiency was 23 % and conversion was 28 %, a 71 % relative increase over conditions without the CDN. Using CFD simulations, we found that the CDN produces a change in the flow geometry, leading to a confined temperature profile at the height of the plasma, and forced extraction of CO to the post-CDN region.